A new broad specificity alkaline metalloprotease from a Pseudomonas sp. isolated from refrigerated milk: role of calcium in improving enzyme productivity - Ertan, Haluk; Cassel, Camilo; Verma, Arjun; Poljak, Anne; Charlton, Tim; Aldrich-Wright, Janice; Mohd Omar, Suhaila; Siddiqui, Khawar Sohail; Cavicchioli, Richardo (Elsevier B.V., 2015)
Metalloproteases represent the largest fraction of the global enzyme market. For biotechnological purposes 31 the accumulation of product (i.e. productivity) provides the best measure of assessing enzyme performance 32 because it takes into account the interplay between activity, stability, activation and inhibition. Studies 33 assessing the productivity of alkaline metalloproteases and chemicals that improve their productivity have 34 not previously been reported. In this study we report the specificity, productivity, kinetic and 35 thermodynamic properties of an extracellular protease, purified from a new strain of Pseudomonas sp. 36 isolated from refrigerated milk. Mass spectrometry analysis revealed the enzyme is a serralysin-type alkaline 37 metalloprotease, with broad cleavage-site specificity. By studying the effects of Ca2+ ion removal (using a 38 chelator) and Ca2+ ion addition, conditions were identified that led to an increase in productivity by 300 % 39 (6.3 vs 1.9 mg azopeptide μg-1 enzyme at 40C). The basis for the enhanced productivity was linked to 40 elevated melting temperatures of secondary (Tm 47 vs 38C) and tertiary structure (Tm 50 vs 44C), 41 increased half-life of inactivation (t1/2 30 vs 4.9 min), increased optimum temperature (44 vs 36C), and 42 changes in both catalytic activity (kcat 3.3 vs 2.2 min-1) and substrate affinity (Km 3.9 vs 2.5 mg ml-1). 43 Thermodynamic data were indicative of Ca2+-binding causing the transition-state to be more ordered (less 44 entropy) relative to the folded-state, thereby resisting a transition to an unfolded state. The specificity, 45 kinetics and response to calcium of this AMP illustrate its potential usefulness for industrial applications, 46 and the research highlights the broader potential for using calcium to enhance the productivity of proteases